Clinical Utility of Charakokta Snehopaga Mahakashaya: A Narrative Review - Puja Nahak; Anup B Thakar; Rahul S Gandhi (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Introduction: Snehopaga Mahakashaya is one of the fifty Mahakashayas enumerated in the fourth chapter of Charaka Samhita Sutra Sthana (Shadvirechanashatashritiya Adhyaya). The term Snehopaga refers to the drugs by incorporating which the properties of unctuous substances like oil or ghee are enhanced to create a synergistic effect and ultimately enhancing the overall therapeutic benefits. These drugs can be employed in dual modes i.e., internally and externally in accordance with the prevailing Doshic imbalance or condition of the disease. So, in this paper an effort is undertaken to shed light on the pharmacological and Ayurvedic qualities of Snehopaga Mahakashaya as well as its potential clinical application in various administration methods. Methodology: Charaka Samhita, Susruta Samhita, and Asthanga Hridaya were thoroughly reviewed to collect formulations containing Snehopaga drugs and their modes of administration. Data were compiled from both direct and indirect references, including details of formulations, indications, routes of administration, and textual sources. The definition of “Snehopaga” was obtained from Charaka and Susruta Samhita. Only formulations and procedures that adhere to the definition of Snehopaga were included, whereas preparations such as Kwatha, Gutika, Churna, and Parisheka etc. were excluded. Pharmaceutical and pharmacological information on Snehopaga drugs was gathered from PubMed and Google Scholar using their botanical names and relevant keywords. Results: The comprehensive review and analysis of the ten drugs categorized under Snehopaga Mahakashaya demonstrated their collective and individual efficacy in supporting Snehana Karma. The concept highlights a unique Ayurvedic strategy, not merely administering oil or ghee for oleation, but enhancing its effect through supportive herbal companions. Conclusion: The Snehopaga Mahakashaya represents a thoughtful formulation strategy in Ayurveda, where herbs are grouped not merely by pharmacological activity but by synergistic action. Its application may enhance efficacy of Snehana therapy and contributes to improve outcomes in cleansing, nourishment and rejuvenation.